2014
DOI: 10.1088/1751-8113/48/2/025204
|View full text |Cite
|
Sign up to set email alerts
|

Lie-point symmetries of the discrete Liouville equation

Abstract: The Liouville equation is well known to be linearizable by a point transformation. It has an infinite dimensional Lie point symmetry algebra isomorphic to a direct sum of two Virasoro algebras. We show that it is not possible to discretize the equation keeping the entire symmetry algebra as point symmetries. We do however construct a difference system approximating the Liouville equation that is invariant under the maximal finite subalgebra SL x (2, R) ⊗ SL y (2, R). The invariant scheme is an explicit one and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(60 citation statements)
references
References 35 publications
2
48
0
10
Order By: Relevance
“…As it is evident from (3.23) there is no way that we can get a Lie point symmetry in agreement with the results presented in [19,20]. The lowest possible symmetry is a generalized symmetry depending on three points (3.25).…”
Section: The Discrete Algebraic Liouville Equationssupporting
confidence: 80%
“…As it is evident from (3.23) there is no way that we can get a Lie point symmetry in agreement with the results presented in [19,20]. The lowest possible symmetry is a generalized symmetry depending on three points (3.25).…”
Section: The Discrete Algebraic Liouville Equationssupporting
confidence: 80%
“…The above normalization condition indicates that all terms in the base (non-invariant) compact scheme, Eq. (32), that include the spatial first derivative will be removed from the compact scheme in the transformed space leading to the following reduced form…”
Section: Viscous Burgers' Equationmentioning
confidence: 99%
“…= e 2s3 (t + s 4 ) λx = e s3 x + s 5 + s 2 (t + s 4 ) λ u = e −s3 (λu + s 1 (x + s 5 ) + s 2 ) (34) ux = e −2s3 (λ 2 u x + s 1 λ) uxx = e −3s3 λ 3 u xxwhere λ = 1 − s 1 (t + s 4 ). As similar to the inviscid Burgers' equation, the scaling symmetry parameter s 3 does not occur when these transformations are implemented to the compact scheme given in Eq (32)…”
mentioning
confidence: 99%
“…In two recent articles [35,36] we dealt with the real hyperbolic Liouville equation as part of a program of discretizing both ordinary and partial differential equations (ODEs and PDEs), while preserving their Lie point symmetries [21,40]. In particular we have shown that it is not possible to preserve the entire infinite-dimensional symmetry group as point symmetries in the discrete case.…”
Section: Introductionmentioning
confidence: 99%
“…For their discretization see [24]. The discretization of PDEs and DODEs preserving their Lie point symmetry groups started in [3,6,11,23,24,35,36,39] and the present article is an integral part of this research. As stated in previous articles there are several aspects to the program.…”
Section: Introductionmentioning
confidence: 99%